Debt relief of natural persons and the rate of satisfaction of their creditors in the Czech Republic - Pasekova, Marie; Fiserova, Zuzana; Crhova, Zuzana; Barinova, Dagmar (Business: Theory and Practice, 2015)
The purpose of this contribution is to ascertain the rate of creditors’ satisfaction in debt relief. The aim of the paper is to set an approximation functions which guarantee a value of 100% of satisfaction of creditors’ receivables for a zero rate of debt and asymptotically nears a level of 30% with an increasing rate of debt. There are two methods used in this paper. Method of analysis was used to analyse of collected data on the course of debt relief of natural person. The method of the ordinary least squares method was used for setting the approximation functions. On the basis of a survey, it was found that individual creditors are satisfied to 50% of their ascertained receivables.